Composition of Prehispanic Diets from Stable Isotope Analysis in Human Remains of the Southern Calchaquíes Valleys, Northwest Argentina (3600–1300 BP) - (:unkn) unknown (Cambridge University Press, 2021)
This article discusses the composition of prehispanic diets based on the isotopic composition (δ13C, δ15N) of 10 human samples dated between 3600 and 1300 BP from the Cajón Valley in Northwest Argentina. The sample is the only one available for the time and region considered and covers a 2,300-year range. It shows long-term tendencies in the consumption of food resources during a time when people were experimenting with and eventually domesticating plants and animals in the high-altitude Southern Calchaquíes valleys. Results indicate that animals contributed more to the diet than was expected and plants correspondingly less than expected. This proportion was maintained even during the human occupations associated with the agropastoral villages of Cardonal and Bordo Marcial (ca. 2000 BP) when a greater contribution of plant resources—in particular maize—would be expected. This new evidence demonstrates the diversity of productive strategies used by the societies of Northwest Argentina at the beginning of the Formative period. A variety of resources contributed to daily food intake, minimizing the importance of maize in the diet.

El presente artículo tiene como objetivo discutir la composición de las dietas prehispánicas basada en la composición isotópica (δ13C, δ15N) de 10 muestras de restos humanos datadas entre 3600 y 1300 años AP, procedentes del Valle del Cajón, Noroeste Argentino. La muestra —única disponible para el período y región considerada— comprende un rango cronológico de 2.300 años indicando tendencias a largo plazo en el consumo de recursos alimentarios durante la etapa de experimentación y domesticación de plantas y animales en los valles altos del sur de los Valles Calchaquíes. Los resultados indican que la dieta incluyó un aporte más sustancial del componente animal con relación al componente vegetal, incluso durante las ocupaciones humanas asociadas a las aldeas agrícolas y pastoriles de Cardonal y Bordo Marcial (ca. 2000 años AP), donde una mayor contribución de las plantas —en especial, el maíz— como recurso dietario era esperada. Esta nueva evidencia permite caracterizar la diversidad de estrategias productivas que debieron tener lugar en los inicios del período Formativo del Noroeste argentino, donde fueron diversos recursos los que sustentaron la alimentación cotidiana de sus habitantes, relativizando la importancia del maíz en la dieta.

Killian Galván, V., Cortés, L., y Rabuffetti, N. (2021). Composition of Prehispanic Diets from Stable Isotope Analysis in Human Remains of the Southern Calchaquíes Valleys, Northwest Argentina (3600–1300 BP). Latin American Antiquity, 32(2), 350-367.
Fil: Killian Galván, Violeta Anahí. Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto Interdisciplinario Tilcara; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina
Fil: Cortés, Leticia Inés. Consejo Nacional de Investigaciones Científicas y Técnicas. Universidad de Buenos Aires. Instituto de las Culturas; Argentina
Fil: Rabuffetti, Nadia. Universidad de Buenos Aires. Facultad de Filosofía y Letras; Argentina
Keywords: Stable isotope analysis; δ13C; δ15N; Prehispanic diets; Northwest Argentina; Plant and animal domestication; Southern Andes; Análisis de isótopos estables; Dietas prehispánicas; Noroeste argentino; Domesticación de plantas y animales; Andes del Sur